Toward territorialised dairy inclusive businesses: insights from an Egyptian case study: making dairy businesses inclusive. Issue 3 (3rd April 2022) - Daburon, Annabelle; Alary, Véronique; Ali, Ahmed; Osman, Mona Abdelzaher; Hosni Abdelsabour, Taha; Tourrand, Jean-Francois
ABSTRACT: Building inclusive businesses with small-scale producers in the agro-food sector presents challenges, most notably in terms of governance and sustainability. These issues were explored through a Danone Egypt Ecosystem Project that sought to promote a replicable business model of milk collection centers to secure a dairy plant's sourcing while contributing to the socio-economic development of smallholders. Quality management was used to link a value chain approach and a localised agri-food system approach. The study showed that an inclusive business relying on non-inclusive coordination had limited efficiency. Decreasing power asymmetries and distances between partners seems central to ensuring sustainability.